Changes to the establishment register and food labelling – selected legal aspects - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2025)
The subject of consideration is selected legal aspects related to the disclosure on food labels of changes made to the entries in the establishment registers. The research attempted to answer the question of whether, in the event of changes to the register, the existing legal regulations sufficiently protect consumers from being misled about the food business operator responsible for providing food information on the label. It also aimed to assess the potential liability on the part of a food business operator for failing to disclose on food labels the change of its name, business name or address entered in the register. As has been established, the current legal regulations sufficiently protect consumers from being misled about food business operators responsible for providing food information in the event of changes to the register. However, with regards food business operators’ liability for not disclosing on the label the changes made to the entries in the establishment register regarding their name, business name or address, it has been found that there are no regulations governing that issue. Therefore the existing legal situation may raise doubts and a legislative intervention seems necessary and justified.